Enhancement of the effect of BCG vaccine against tuberculosis using DDA/TDB liposomes containing a fusion protein of HspX, PPE44, and EsxV - Davood Mansury; Kiarash Ghazvini; Saeid Amel Jamehdar; Ali Badiee; Mohsen Tafaghodi; Amin Reza Nikpoor; Yousef Amini; Mahmoud Reza Jaafari (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Tuberculosis has been a major health problem worldwide for years; therefore, it is important to develop and produce an effective vaccine against this disease. In this study, the immunogenicity of Mycobacterium tuberculosis fusion protein (FP) encapsulated in liposomes containing DDA/TDB was evaluated. The FP was expressed in E. coli BL21 and encapsulated in liposomal formulations. Three weeks after the last subcutaneous immunization, IFN-γ, IL-4, IL-17, and IL-12 in spleen cell culture supernatants, and IgG2a, IgG1, and IgG2b titres in sera were measured. The greatest IFN-γ and IL-12 interleukin concentrations were observed in the DDA/TDB/CHOL liposomes containing the FP. Initial injection with BCG improved the efficacy of the DDA/TDB/CHOL/FP vaccine. The IgG2a/IgG1 ratio was also high in the DDA/TDB/CHOL/FP group; furthermore, the IgG2a/IgG1 ratio was increased in the BCG-primed, DDA/TDB/CHOL/FP-boosted group, indicating induction of a cellular immune response. Our study showed that the FP-containing DDA/TDB/CHOL liposomes induced a Th1 response. However, the groups that first received BCG and then DDA/TDB/CHOL/FP had the greatest Th1 response in terms of IFN-γ and IL-12 production of all the groups. This suggests that these formulations enhance the BCG vaccine’s effectiveness.